Arginine Vasotocin Regulation of Interspecific Cooperative Behaviour in a Cleaner Fish - Soares, Marta C.; Bshary, Redouan; Mendonça, Rute; Grutter, Alexandra S.; Oliveira, Rui F. (PLOS ONE, 2012)
In an interspecific cooperative context, individuals must be prepared to tolerate close interactive proximity to other species but also need to be able to respond to relevant social stimuli in the most appropriate manner. The neuropeptides vasopressin and oxytocin and their non-mammalian homologues have been implicated in the evolution of sociality and in the regulation of social behaviour across vertebrates. However, little is known about the underlying physiological mechanisms of interspecific cooperative interactions. In interspecific cleaning mutualisms, interactions functionally resemble most intraspecific social interactions. Here we provide the first empirical evidence that arginine vasotocin (AVT), a non-mammalian homologue of arginine vasopressin (AVP), plays a critical role as moderator of interspecific behaviour in the best studied and ubiquitous marine cleaning mutualism involving the Indo-Pacific bluestreak cleaner wrasse Labroides dimidiatus. Exogenous administration of AVT caused a substantial decrease of most interspecific cleaning activities, without similarly affecting the expression of conspecific directed behaviour, which suggests a differential effect of AVT on cleaning behaviour and not a general effect on social behaviour. Furthermore, the AVP-V1a receptor antagonist (manning compound) induced a higher likelihood for cleaners to engage in cleaning interactions and also to increase their levels of dishonesty towards clients. The present findings extend the knowledge of neuropeptide effects on social interactions beyond the study of their influence on conspecific social behaviour. Our evidence demonstrates that AVT pathways might play a pivotal role in the regulation of interspecific cooperative behaviour and conspecific social behaviour among stabilized pairs of cleaner fish. Moreover, our results suggest that the role of AVT as a neurochemical regulator of social behaviour may have been co-opted in the evolution of cooperative behaviour in an interspecific context, a hypothesis that is amenable to further testing on the potential direct central mechanism involved.